Studi Eksperimen Pengaruh Jumlah Sudu Terhadap Kinerja Wind Turbine Crossflow - Fahrudin, Fahrudin; Wahyuni, Fitri; Oktavitasari, Dini (Mechanical Engineering Department - Semarang State Polytechnic, 2021)
Wind is an alternative energy that is environmentally friendly and sustainable. Therefore, we need a type of wind turbine that can receive wind from all directions. The crossflow type vertical axis wind turbine has a high torque coefficient at a low tip speed ratio. The purpose of this study was to determine the effect of the number of blades on the performance of the vertical axis crossflow wind turbine. The experimental test was carried out by varying the number of blades. The configuration is analyzed using the experimental wind tunnel test scheme which has been modified in the section test section. The results showed that the number of blades 16 has a power coefficient ( ) = 0.23 tip speed ratio (TSR) = 0.42 at a wind speed of 4 m / s.